The Smirnov compactification as a quotient space of the Stone-Čech compactification - T. B. M. McMaster (International Journal of Mathematics and Mathematical Sciences)
For a separated proximity space, a decomposition of the Stone-Čech compactification is presented which produces the Smirnov compactification and its basic properties by elementary arguments without recourse to clusters or totally bounded uniformities.